Online teaching during COVID19 pandemic in different medical Institutions of West Bengal- From student’s perspective - Saha, Bhaskar; Halder, Mrityunjoy; Mandal, Mita; Das, Subir Kumar (Asian Journal of Medical Sciences, 2021)
Background: Social distancing is important preventive strategy to prevent spreading of SARSCOV-2. The medical faculties are continuing the teaching-learning session using different online platform. Aims and Objective: This online survey aims at exploring the different aspect of online teaching effects among medical students. Materials and Methods: Forty-four validated questions in the Google survey form were distributed among the MBBS students of different medical colleges of West Bengal in this cross-sectional study, and analysed. Results: The responses from 416 participants show that internet-based teaching has been adopted by 96.4% of colleges. Practical class and classes regarding clinical exposure are the two most neglected section of the MBBS curriculum during this pandemic. Total teaching hours per day also drastically reduced from mean of 5.56 h/ day in pre-pandemic time to 1.95 h/ day during this pandemic. Out of 69.7% of the participants who faced difficulty in following online classes, majority (56.25%) was due to technical problems including issues related to internet connectivity and software. Participants were of opinion that current session should be extended on an average of 3 months as the practical and clinical classes are way behind in syllabus completion. According to 72.35% of participants, online classes are less effective than the offline classes. Conclusions: In nutshell, online teaching activities cannot replace the classical classroom teaching, though it is a cost-effective and viable method during this pandemic period.